Konsep Pertanggungjawaban Pidana Dalam Hukum Pidana Nasional Yang Akan Datang - Boy Dippu Tua Simbolon; Kezia Thasa Emteta Karina Bangun; Reh Bungana Br PA; Maulana Ibrahim (Jurnal Relasi Publik, 2023)
The concept of criminal responsibility in national criminal law is the main basis for determining sanctions or punishment for violations of criminal law. In the future era, criminal responsibility is expected to continue to develop and adapt to developments in society, technology and existing legal values. In facing the future, the concept of criminal responsibility is expected to become more progressive, fair and in line with the demands of social justice. Improving the quality of punishment and the effectiveness of the criminal justice system needs to be the main focus, taking into account the principles of human rights, protection of minorities and restorative justice. In addition, the importance of a preventive approach in national criminal law will be increasingly emphasized. Efforts to prevent criminal acts through education, rehabilitation and community empowerment are expected to reduce crime rates and create a safer environment. In the context of globalization, collaboration between countries in tackling cross-border crime needs to be strengthened. International agreements on extradition, exchange of information, and harmonization of criminal law can be strategic steps to increase the effectiveness of law enforcement. By updating the concept of criminal responsibility in national criminal law, it is hoped that a legal system that is adaptive, responsive and can better respond to future challenges can be created. In this way, security and justice in society can be more optimally maintained, in line with the main objective of criminal law to create order and protection for all citizens.